New Guaianolide Sesquiterpene Lactones and Other Constituents from Pyrethrum pulchrum - Erdenetsogt, Uugangerel; Nadmid, Suvd; Paetz, Christian; Dahse, Hans-Martin; Voigt, Kerstin; Gotov, Choijamts; Boland, Wilhelm; Dagvadorj, Enkhmaa (Planta Medica, 2021)
Pyrethrum pulchrum is a rare Mongolian plant species that has been traditionally used as an ingredient in various remedies. Bioactivity-guided fractionation performed on the methanol extract of its aerial parts led to the isolation of 2 previously undescribed guaianolide-type sesquiterpene lactones, namely 1β,10β-epoxy-8α-hydroxyguaia-3,11(13)-dien-6,12-olide (1) and 1,8,10-trihydroxyguaia-3,11(13)-dien-6,12-olide (2), along with the isolation or chromatographic identification of 11 compounds, arglabin (3), 3β-hydroxycostunolide (4), isocostic acid (5), (E)-9-(2-thienyl)-6-nonen-8-yn-3-ol (6), (Z)-9-(2-thienyl)-6-nonen-8-yn-3-ol (7), N1,N5,N10,N14-tetra-p-coumaroyl spermine (8), chlorogenic acid (9), 3,5-di-O-caffeoylquinic acid (10), 3,5-di-O-caffeoylquinic acid methyl ester (11), 3,4-di-O-caffeoylquinic acid (12), and tryptophan (13). Their structures were assigned based on spectroscopic and spectrometric data. The antimicrobial, antiproliferative and cytotoxic activities of selected compounds were evaluated. The new compounds showed weak to moderate antimicrobial activity. Arglabin (3), the major sesquiterpene lactone found in the methanol extract of P. pulchrum, exhibited the highest activity against human cancer lines, while compound 1 also possesses significant antiproliferative activity against leukemia cells.
Keywords: Pyrethrum pulchrum; Asteraceae; sesquiterpene lactone; antiproliferative effect; cytotoxicity; leukemia cell lines